2016
DOI: 10.4049/jimmunol.1501232
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of CD8+ T Cells Exacerbates CD4+ T Cell–Induced Monocyte-to-Fibroblast Transition in Renal Fibrosis

Abstract: Bone marrow–derived monocyte-to-fibroblast transition is a key step in renal fibrosis pathogenesis, which is regulated by the inflammatory microenvironment. However, the mechanism by which the inflammatory microenvironment regulates this transition is not fully understood. In this study, we examined how the CD8+ T cell/IFN-γ microenvironment regulates the monocyte-to-fibroblast transition in renal fibrosis. Genetic ablation of CD8 promoted a monocyte-to-fibroblast transition and increased renal interstitial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…15,16 MMP9 activity was inhibited using MMP9 inhibitor or MMP9-neutralizing antibody, which was administered daily for four consecutive days from day 0 to 3 (for early stage of UUO), 6 to 9 (for mid stage) or 10 to 13 (for late stage). 1,10,[21][22][23][24] Therefore, we hypothesized that neutrophil infiltration enhances renal fibrosis by promoting the expansion of inflammation and macrophage accumulation in the obstructed kidney; moreover, neutrophil produces MMP9 in the kidney to promote macrophage infiltration. Many reports demonstrated that inflammatory cells, including neutrophils, produce MMP9 during tissue injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 MMP9 activity was inhibited using MMP9 inhibitor or MMP9-neutralizing antibody, which was administered daily for four consecutive days from day 0 to 3 (for early stage of UUO), 6 to 9 (for mid stage) or 10 to 13 (for late stage). 1,10,[21][22][23][24] Therefore, we hypothesized that neutrophil infiltration enhances renal fibrosis by promoting the expansion of inflammation and macrophage accumulation in the obstructed kidney; moreover, neutrophil produces MMP9 in the kidney to promote macrophage infiltration. Many reports demonstrated that inflammatory cells, including neutrophils, produce MMP9 during tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…10,[17][18][19][20] Previous results by us and other researchers also demonstrated that the early stage of UUO is the progression of inflammatory cell infiltration, and a high peak occurred from days 3-7. 1,10,[21][22][23][24] Therefore, we hypothesized that neutrophil infiltration enhances renal fibrosis by promoting the expansion of inflammation and macrophage accumulation in the obstructed kidney; moreover, neutrophil produces MMP9 in the kidney to promote macrophage infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the role of interstitial fibroblast proliferation, there were studies indicating that bone marrow-derived fibroblast precursors contributed significantly to the development of renal fibrosis [11, 12]. Previous research demonstrated that activation of proinflammatory cytokines contributed substantially to the development of renal interstitial fibrosis [13, 14]. Moreover, mounting evidence in vivo and in vitro has indicated that PTEN mediates multiple signal pathways involved in the pathophysiologic process of fibrosis in the kidney such as SMAD3, p53, and JNK[15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…To discover the reason why IRF‐1 can decrease Klotho transcription, we analyzed the sequence of putative promoter region of human Klotho gene. Bioinformatics analysis from all of the three databases (PROMO, Genecards and JASPAR) predicted 11 transcriptional factors that could bind to Klotho promoter region (the relative score is above 80 points) (Figure A).Nine transcriptional factors (C/EBP‐β, PPAR‐γ, p53, SP1, YY1, USF2, C/EBP‐α, GATA3, and ATF3) have been found to participate in renal fibrosis . Next, we detected which of the above transcription factors are regulated by IRF‐1 in tubular epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Nine transcriptional factors (C/EBP-β, PPAR-γ, p53, SP1, YY1, USF2, C/EBP-α, GATA3, and ATF3) have been found to participate in renal fibrosis. [30][31][32][33][34][35][36][37][38] Next, we detected which of the above transcription factors are regulated by IRF-1 in tubular epithelial cells. Our results show that mRNA level of four transcriptional factors (SP1, C/EBP-β, YY1, and C/EBP-α) were significantly changed after transfection with IRF-1 vector.…”
Section: Irf-1 Inhibits Klotho Expression Via Inactivation Of C/ebp-βmentioning
confidence: 99%